Karakteristik Lokal Pengrajin Gerabah Terhadap Kualitas Produk Gerabah Desa Maregam Kota Tidore Kepulauan - Kusrini Kusrini (UNM Geographic Journal, 2019)
The study was carried out in Maregam Village, South Tidore District, Tidore Islands City. This study aims to determine the local characteristics of pottery craftsmen on the quality of the products produced. The number of pottery craftsmen in the village of Maregam is 66 households. Pottery is only done by women (wives) who have inherited it from generation to generation and has become a tradition in the community in the village of Maregam. Making pottery is one of the main livelihoods for residents of Maregam Village besides fishermen and farmers. This research is descriptive using secondary data and field survey data with a questionnaire instrument and direct interviews with key informants at the research location with triangulation data analysis.Penelitian dilaksanakan di Desa Maregam, Kecamatan Tidore Selatan Kota Tidore Kepulauan. Penelitian ini bertujuan untuk mengetahui karakteristik lokal pengrajin gerabah terhadap kualitas produk yang dihasilkan. Jumlah pengrajin gerabah di desa Maregam terdapat 66 KK. Kerajinan gerabah hanya dikerjakan oleh kaum perempuan (istri) yang telah mewarisinya secara turun temurun serta sudah menjadi tradisi dalam masyarakat di Desa Maregam. Pembuatan gerabah merupakan  salah satu mata pencaharian utama untuk penduduk Desa Maregam selain nelayan dan petani. Penelitian ini bersifat deskriptif menggunakan data sekunder dan data survey lapangan dengan alat instrument kuesioner dan wawancara langsung terhadap informan kunci di lokasi penelitian dengan analisis data triangulasi.